(untitled) (Bangladesh Veterinarian, 2012)
Sixteen female Black Bengal goats (10 ± 0.6 months of age and 11.5 ± 1.3 kg live weight) were divided into four groups having four goats in each. In a completely randomized design, A, B, C and D were given 150, 200, 250 and 300g concentrate mixture with ad libitum green grasses. Total dry matter (DM) intake (333.6, 374.7, 416.3 and 456.5g/day in groups A, B, C and D, respectively) was significantly (P<0.01) influenced by the level of concentrate in the diet. Crude protein (CP) intake (45.2, 57.0, 66.4 and 75.7g/day) was significantly (P<0.01) higher in group D and lower in group A. Daily weight gain of kids did not differ significantly between groups. Feed and protein conversion efficiency was not significantly influenced by the concentrate level in the diet. Milk yield was significantly (P<0.01) increased (206.8, 233.4, 359.3 and 374.7 mL/day for groups A, B, C and D, respectively) with the supplementation of concentrate. It is suggested to supplement 250g of concentrate daily to female goats in addition to ad libitum roughage. DOI: http://dx.doi.org/10.3329/bvet.v29i1.11884 Bangl. vet. 2012. Vol. 29, No. 1, 7-16